The response of real estate investment trust returns to the inflation and the industrial production in Malaysia / Siti Norbaizura Mohd Sudas - Mohd Sudas, Siti Norbaizura (2007)
Real estate investment trust (REITs) is related with an investment fund designed to invest in various real estate properties. It is similar to a stock or bond mutual fund, except that the money provided by the investors is invested in property and buildings rather than in stocks and bonds. Real estate investment trust (REITs) return has some connection with the macroeconomic variables such as inflation and industrial production in the economy circulation of investment. The issue that is relating with the inflation and money supply has generated discussion in recent years. Thus, the purpose of the research is to determine the relationship between real estate investment trust (REITs) return with the inflation and industrial production in Malaysia scenario. To analyze the relationship between real estate investments trusts (REITs) return with inflation and real economic activity (industrial production), this study using the real estate investment trust (REITs) sector which has been listed in Bursa Malaysia. The time horizon between 1998 and 2006. Sample data consists of 108 monthly stock prices / returns, consumer price index and industrial production index. Multiple regressions were used as a methodology in this study. There are some previous researchers have concluded that there are positive relationship between real estate investment trust (REITs) returns with the inflation and real economic activity such as Miles and Mahoney (1997) and Adrangi et.al (2003). There are also some of them says oppositely which there is negative relationship as stated by Ewing and Payne (2005). Future researchers also can use this study as their guideline to know the effect of real estate investment trust (REITs) returns with the macroeconomic variables such as inflation and industrial production.